The Effects of High School Course Taking and SAT Scores On College Major Selection - Alparslan Şahin; Jim Morgan; Mary Capraro; Niyazi Erdoğan; Robert Capraro (Sakarya University, 2013)
A survey study design was employed to examine the relationship between enrollment in computer and Advanced Placement courses during high school, SAT scores and subsequent selection of a STEM major in post-secondary education. Study data were collected through an online survey from a multi-school charter school system in which a variety of computer courses are offered to 9-12 grade students. The study showed that students' scores on the SAT reading section and, total composite score (reading + mathematics) had a statistically significant relationship with students' selection of a science, engineering, technology, and mathematics [STEM] major. Although there was not a statistically significant relationship between students' SAT mathematics scores, there was a pattern showing that students with higher SAT mathematics scores were more likely to choose a STEM major. We also found that there was a statistically significant relationship between the number of AP science courses and total number of AP courses taken by students and their selection of a STEM major. The final analysis revealed that there was no statistically significant difference between those who chose STEM majors and the number of computer courses taken.